Initial Feasibility Study to Drill and Core the Ocean Mantle - Nicolas Pilisi (Scientific Drilling, 2011)
An initial feasibility study (Pilisi and Whitney, 2011) of drilling through the Mohorovičić discontinuity (Moho) into the oceanic mantle specifically focused on future requirements for planning, drilling and coring a hole 500 m into the oceanic mantle from three candidate locations in the Pacific Ocean (Cocos Plate, Baja California, and offshore Hawaii). The study points out some of the critical issues that need to be resolved before embarking upon such a challengingproject. It was conducted on the basis of data provided by the Integrated Ocean Drilling Program–Management International (IODP-MI), the Center for Deep Earth Exploration (CDEX) operating the drilling vessel Chikyu within IODP, public domain information, and past experience that Blade Energy Partners (hereafter mentioned as “Blade”; http://www.blade-energy.com/) has had with frontier projects in the offshore deepwater oil and gas and geothermal industries.